Effect of Nurse-Led Consultations on Post-Traumatic Stress and Sense of Coherence in Discharged ICU Patients With Clinically Relevant Post-Traumatic Stress Symptoms—A Randomized Controlled Trial. Issue 12 (December 2020) - Valsø, Åse; Rustøen, Tone; Småstuen, Milada Cvancarova; Ekeberg, Øivind; Skogstad, Laila; Schou-Bredal, Inger; Myhren, Hilde; Sunde, Kjetil; Tøien, Kirsti
Abstract : Objectives: To investigate the effect of nurse-led consultations on reducing post-traumatic stress symptoms and increasing sense of coherence in discharged ICU patients with clinically relevant post-traumatic stress symptoms and to identify variables associated with symptoms 12 months later. Design: A pragmatic nonblinded randomized controlled trial. Settings: Five surgical and medical ICUs at Oslo University Hospital. Patients: Adult patients treated in the ICU greater than or equal to 24 hours were screened with Post-Traumatic Stress Scale 10 intensive part B after ICU discharge. Those scoring greater than or equal to 25 were included in the study. Intervention: Patients randomized to intervention group were offered three nurse-led consultations within 2 months, and patients in the control group received standard care. Measurements and Main Results: Sense of Coherence Scale 13 and Post-Traumatic Stress Scale 10 intensive part B were completed after inclusion, and reevaluated after 3, 6, and 12 months. Linear mixed model for repeated measures and linear regression analyses were performed. Among 523 screened patients, 111 and 113 were randomized to intervention group and control group, respectively. Mean Post-Traumatic Stress Scale 10 intensive part B score was 37 (±10) before randomization. No differences in post-traumatic stress symptoms or sense of coherence were found between intervention group versus control group, with a mean Post-Traumatic Stress Scale 10 intensive part B score 39 (95% CI, 37–41) versus 37 (95% CI, 35–39), 32 (95% CI, 28–35) versus 32 (95% CI, 29–35), 31 (95% CI, 28–34) versus 30 (95% CI, 27–33), and 31 (95% CI, 28–34) versus 29 (95% CI, 26–33) at baseline, 3, 6, and 12 months, respectively. There was a significantly reduced Post-Traumatic Stress Scale 10 intensive part B score for both groups during the year ( p = 0.001). Low sense of coherence, pain, and previous psychiatric problems were associated with increased level of post-traumatic stress symptoms at 12 months. Conclusions: Nurse-led consultations did not reveal any significant effect on post-traumatic stress symptoms or sense of coherence after ICU discharge in patients with clinically relevant symptoms. Abstract : Supplemental Digital Content is available in the text.